Analisis Kinerja Jalan Raya Kota Malang Menggunakan Metode FCD (Floating Car Data) - Mega Satya Ciptaningrum; Muhammad Aziz Muslim; Agus Naba (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
Congestion is one of the symptoms of inadequate road conditions and interaction between the traffic elements that affect the performance of the highway. Methods of measuring the performance of the highway have been reported in Manual Kapasitas Jalan Indonesia in 1997. Highway performance measurement parameters that can be used are speed and time delay. Floating Car Data (FCD) is a method to retrieve data such as speed and time delay quickly and efficiently. While Adaptive Neuro Fuzzy Inference System (ANFIS) can be used as a method of measuring the performance of the FCD method. In this study, the FCD method is applied to the segment of urban roads in the city of Malang by utilizing the GPS feature on a mobile device carried by the rider. The results of data recording by FCD are tested using ANFIS with two input parameters (speed and time delay) and one output (congestion level). Results of experiments using 70% training data and 30% test data are able to obtain maximum performance, with the lowest MSE is 0.43, while the calculated travel speed results of the FCD method compared with the base flow speed (based on MKJI) is 68.22% during spare time, and 43.96% during traffic jam.